LOCAL GEOMETRICAL ANALYSIS OF 3D POROUS NETWORKS BASED ON THE MEDIAL AXIS: APPLICATION TO BONE MICROARCHITECTURE MICROTOMOGRAPHY IMAGES - Peyrin, Françoise; Peter, Zsolt; Larrue, Aymeric; Bonnassie, Alexandra; Attali, Dominique (Image Analysis and Stereology, 2011)
This paper proposes a new method for local evaluation the geometry of complex 3D porous networks such as bone micro-architecture. The method described here allows local quantification of the geometry of the entire volume. It is well adapted to high resolution images where the voxel size is smaller than the structure thickness. The classification of each point on the medial axis is based on a local topological analysis of a neighbourhood, the size of which is adapted locally to the studied point. This property makes this classification more robust to the small irregularities that may appear in a real biological data set. After classification, new quantitative parameters of bone micro-architecture characterizing plate and rod structures are independently defined. The method is quantitatively evaluated on numerical phantoms presenting shape irregularities. Application to experimental 3D bone microtomographic images shows that the method provides visually correct results, even on complex natural trabecular structures. The additional geometrical parameters provided by this method allow discrimination of volumes whose porosity and mean thickness are similar.